Exploiting the Concept of Multivalency with 68Ga- and 89Zr-Labelled Fusarinine C-Minigastrin Bioconjugates for Targeting CCK2R Expression. (10th April 2018) - Summer, Dominik; Rangger, Christine; Klingler, Maximilian; Laverman, Peter; Franssen, Gerben M.; Lechner, Beatrix E.; Orasch, Thomas; Haas, Hubertus; von Guggenberg, Elisabeth; Decristoforo, Clemens
Abstract : Cholecystokinin-2 receptors (CCK2R) are overexpressed in a variety of malignant diseases and therefore have gained certain attention for peptide receptor radionuclide imaging. Among extensive approaches to improve pharmacokinetics and metabolic stability of minigastrin (MG) based radioligands, the concept of multivalency for enhanced tumour targeting has not been investigated extensively. We therefore utilized fusarinine C (FSC) as chelating scaffold for novel mono-, di-, and trimeric bioconjugates for targeting CCK2R expression. FSC-based imaging probes were radiolabelled with positron emitting radionuclides (gallium-68 and zirconium-89) and characterized in vitro (log ⁡ D, IC50, and cell uptake) and in vivo (metabolic stability in BALB/c mice, biodistribution profile, and microPET/CT imaging in A431-CCK2R/A431-mock tumour xenografted BALB/c nude mice). Improved targeting did not fully correlate with the grade of multimerization. The divalent probe showed higher receptor affinity and increased CCK2R mediated cell uptake while the trimer remained comparable to the monomer. In vivo biodistribution studies 1 h after administration of the 68 Ga-labelled radioligands confirmed this trend, but imaging at late time point (24 h) with 89 Zr-labelled counterparts showed a clearly enhanced imaging contrast of the trimeric probe compared to the mono- and dimer. Furthermore, in vivo stability studies showed a higher metabolic stability for multimeric probes compared to the monomeric bioconjugate. In summary, we could show that FSC can be utilized as suitable scaffold for novel mono- and multivalent imaging probes for CCK2R-related malignancies with partly improved targeting properties for multivalent conjugates. The increased tumour accumulation of the trimer 24 h postinjection (p.i.) can be explained by slower clearance and increased metabolic stability of multimeric conjugates.